Cylindrical Bounded Quaternion Control for Tracking and Surrounding a Ground Target Using UAVs. Issue 2 (2020) - Abaunza, Hernan; Castillo, Pedro; Theilliol, Didier; Belkadi, Adel; Ciarletta, Laurent
Abstract: A cooperative tracking algorithm for multiple quadrotors autonomously tracking and surrounding a target ground vehicle is presented in this paper. A nonlinear bounded controller is proposed using geometrical functions to stabilize the translational and rotational dynamics using bounded 3-dimensional control inputs, employing quaternion properties and operators in its design, Lyapunov theory is used to prove system stability. The navigation challenge is tackled by proposing a cost function based on the desired behavior of the aerial vehicles for tracking and surrounding the target, which is solved by finding the optimal solution with a Particle Swarm Optimization algorithm. Simulations and experimental results corroborate the good performance of the scheme.